Anima animus: Jennifer Jason Leigh's bisexual method in Last Exit to Brooklyn - Ian Murphy (Alphaville: Journal of Film and Screen Media, 2012)
This essay explores Jennifer Jason Leigh’s portrayal of the young prostitute Tralala in Last Exit to Brooklyn (Uli Edel, 1989) as a case study in performance style that can be usefully understood as bisexual. Drawing firstly upon Joan Riviere’s concept of womanliness as a masquerade, it examines how Tralala’s feminine performativity masks a confused, neurotic and androgynous gender identity and a raging bid for phallic power. As played by Leigh, Tralala’s snarling speech and undulating swagger evokes the wounded rage, rebellion and alienation of 1950s Method “bad boy” stars such as Marlon Brando, James Dean and Montgomery Clift, and the result is a performance style that oscillates freely between male and female subjectivities. Reading the male Method stars in terms of alternative masculinities that transgress the social order, the article argues that Tralala’s essential masochism is fuelled by a similar disavowal of her biological gender. In this regard, she demonstrates a desire to annihilate the self that has less to do with standard screen representations of female masochism than with the explosive psychic processes of classic Method masculinity.